Tackling childhood anemia in malaria zones: comprehensive strategies, challenges, and future directions - Emmanuel Ifeanyi Obeagu; Getrude Uzoma Obeagu (Academia Medicine)
Childhood anemia persists as a global health concern, with heightened significance in regions endemic to malaria. This review synthesizes current knowledge on the strategies used to address childhood anemia in malaria-prone areas, examining the complex interplay between these two health challenges. The epidemiology of childhood anemia in malaria-endemic regions is explored, emphasizing the impact of malaria on anemia development. Existing interventions, including antimalarial drugs, nutritional supplements, and preventive measures, are critically assessed. Despite progress, challenges in anemia management persist, driven by issues of healthcare access, socioeconomic factors, and evolving malaria strains. The review advocates for integrated approaches and multidisciplinary collaboration to address the multifaceted nature of the problem. Future directions, including emerging trends and innovations, are discussed, offering insights into potential transformative strategies for improved pediatric health outcomes in malaria-affected regions. This comprehensive analysis contributes to the ongoing dialogue on mitigating childhood anemia in the context of malaria and guides future research and intervention efforts.